PENGARUH PEMAHAMAN, KESADARAN, KUALITAS PELAYANAN DAN KETEGASAN SANKSI TERHADAP KEPATUHAN WPOP - LAURA LAURA; IMAN AKHADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to obtain empirical evidence and examine the influence of independent variables, namely understanding, awareness, quality of services, strictness of sanction, modernization of the tax administration system and tax socialization. On the dependent variable, namely compliance individual taxpayers. Taxpayers registered in DKI Jakarta are the population in this study. Meanwhile, this study used a sample of 104 respondents, namely individual taxpayers who work as an entrepreneur and have NPWP which is in West Jakarta region. The sampling technique researchers use in one type of non-probability sampling, namely convenience sampling or accidental sampling. The instrument used to collect data in this study was a closed questionnaire. The result given in this research are; modernization of tax administration have an influence on compliance of individual taxpayers. While understanding, awareness, quality of services, strictness of sanction and tax socialization do not have an influence on compliance of individual taxpayers.